Recording and voice processing 2 working in the studio - Reveillac, Jean-Michel (Waves series., 2022)
Capturing, recording and broadcasting the voice is often difficult. Many factors must be taken into account and achieving a true representation is much more complex than one might think. The capture devices such as the position of the singer(s) or narrator(s), the acoustics, atmosphere and equipment are just some of the physical aspects that need to be mastered. Then there is the passage through the analog or digital channel, which disrupts the audio signal, as well as the processes that are often required to enrich, improve or even transform the vocal timbre and tessitura. While in the past these processes were purely material, today digital technologies and software produce surprising results that every professional in recording and broadcasting should know how to master. Recording and Voice Processing 2 focuses on live and studio voice recordings. It presents the various pieces of hardware and software necessary for voice recording, and details possible sound channel configurations based on recording location. An actual recording, and its various constraints, is then considered, addressing the pitfalls to avoid and the strategies to use in order to achieve a satisfactory result. Different special effects (vocoder, auto-tune, Melodyne, etc.) that can be used on the voice, whether spoken or sung, are also presented.